Relasi Antara Agama dan Media Baru - Haqqi Annazilli (JURNAL ILMIAH SYI'AR, 2018)
Media is not something foreign in this era, but media is still a central part of communication, new media is still new or more widely used by individuals who always communicate, the more sophisticated media that is used will make everyone more eager to communicate in verbal or non verbal forms. Such as the new media that developed in this century is the internet which, according to some people, is something miraculous, but what exactly is it looking for from the new media? Until when can this media survive and be used properly? With the advancement of information and communication technology in this era, news from abroad is so quickly conveyed, long-distance communication can be done face to face. It is undeniable that modern life has been felt by various layers of society. New media is a term to describe the emergence of a new era in communication or interaction, computers, information networks and communication. If traced further the media turns out to bring a new theology (new theology) in religion. Almost all of the people are looking for sources of religious law or theological basis of new media (theology on new media). These conditions are increasingly apparent with the advent of the internet or what is called new media. New media or the internet bring new values in religion for some people. So that with the presence of these new media, some people tend to take religious values through the media.